Molecular approaches for blood meal analysis and species identification of mosquitoes (Insecta: Diptera: Culicidae) in rural locations in southern England, United Kingdom - Hernández-Triana, Luis Miguel; Brugman, Victor Albert; Prosser, Sean Williams John; Weland, Chris; Nikolova, Nadya; Thorne, Leigh; Marco, Mar Fernández De; Fooks, Anthony Richard; Johnson, Nicholas (Zootaxa, 2017)
Thirty-four species of Culicidae are present in the UK, of which 15 have been implicated as potential vectors of arthropod-borne viruses such as West Nile virus. Identification of mosquito feeding preferences is paramount to the understanding of vector-host-pathogen interactions which, in turn, would assist in the control of disease outbreaks. Results are presented on the application of DNA barcoding for vertebrate species identification in blood-fed female mosquitoes in rural locations. Blood-fed females (n = 134) were collected in southern England from rural sites and identified based on morphological criteria. Blood meals from 59 specimens (44%) were identified as feeding on eight hosts: European rabbit, cow, human, barn swallow, dog, great tit, magpie and blackbird. Analysis of the cytochrome c oxidase subunit I mtDNA barcoding region and the internal transcribed spacer 2 rDNA region of the specimens morphologically identified as Anopheles maculipennis s.l. revealed the presence of An. atroparvus and An. messeae. A similar analysis of specimens morphologically identified as Culex pipiens/Cx. torrentium showed all specimens to be Cx. pipiens (typical form). This study demonstrates the importance of using molecular techniques to support species-level identification in blood-fed mosquitoes to maximize the information obtained in studies investigating host feeding patterns.